Defensive tradeoffs are not prerequisites to plant diversity in a two species model. Issue 1 (5th July 2017) - Mortensen, Brent; Abbott, Karen C.; Danielson, Brent
Abstract : Trait‐based theories of biodiversity consider interspecific tradeoffs among species‐specific traits as prerequisites to maintaining community evenness, a component of species diversity. Such tradeoffs are commonly observed in plant communities, particularly in relation to traits associated with resistance to herbivory. Indeed, global experiments show that interspecific tradeoffs are common between plant defense and growth or competitive ability; however, the positive effects of herbivory on plant diversity predicted by theories with trait‐based tradeoffs are far less commonly observed. Moreover, both the overall and relative importance of these tradeoffs in promoting plant diversity are not well known. To disentangle the relationships among growth, competition, and defense in relation to plant community evenness, we built a model that describes the effects of a shared herbivore on two plant species with the potential to differ in each of these traits. While tradeoffs between plant defense and growth or competitive ability can increase plant diversity via evenness, this is not always the case nor is it a requirement for increased diversity. Herbivores may increase plant diversity even in the absence of defensive tradeoffs, preferentially consuming apparently maladapted species, by limiting the negative effects of interspecific interactions. Therefore, the importance of defensive tradeoffs in increasing diversity may not be as important, or as straightforward, as previously hypothesized.